IMPROVING THE STUDENTS’ WRITING ABILITY THROUGH IMAGINATION IN CREATIVE WRITING MATERIAL AT MA DDI BABURRIDHA SAWERE, BULUKUMBA - Anwar (Journal of Innovation Research and Knowledge, 2022)
This research is about Improving the students’ Writing Ability through Imagination in Creative Writing Material at MA DDI Baburridha Sawere, Bulukumba. The problem statement is whether the use of imaginative writing material improves the writing ability of the students at MA DDI Baburridha Sawere. The objective of this research was to find out the description about the imaginative writing materials, whether or not it can improve the students’ ability in writing. This research applied pre-experimental method using one group pre-test and pos-test design to students who consisted of 74 students. The samples of the research consisted of 29 students who were chosen by using purposive sampling. The data collected through written tests. The result of the data indicated that there was a significant difference between students’ pre-test and students’ post-test. The total mean of post-test (83.5) was greater than the total mean of pre-test (67.5). From t-test, the researcher found that the value of t-test (83.5) was greater than t-table (2.052) at the level of significance 0.05 with degree of freedom (df) = 28. Based on the finding of the research, the researcher drew a conclusion that the Imagination in Creative Writing Material increased the students’ ability in writing at MA DDI Baburridha Sawere, Bulukumba.